A case–control study of childhood trauma in the development of irritable bowel syndrome. Issue 7 (11th May 2014) - Halland, M.; Almazar, A.; Lee, R.; Atkinson, E.; Larson, J.; Talley, N. J.; Saito, Y. A.
Abstract Background The etiology of irritable bowel syndrome (IBS) is not been fully elucidated, but childhood trauma may disturb the brain–gut axis and therefore be important. Thus, we conducted a family based case–control study of IBS cases and their relatives with the aims to (i) determine the frequency of childhood trauma among IBS cases and controls as well as their relatives, and (ii) assess childhood trauma among IBS cases with affected relatives (familial IBS). Methods Outpatients with IBS, matched controls, and their first‐degree relatives completed a self‐report version of Bremner' Early Trauma Inventory. Percent of cases and controls with a family history were compared and odds ratios were computed using chi‐squared test; recurrence risks to relatives were computed using logistic regression and generalized estimating equations. Key Results Data were collected from 409 cases, 415 controls, 825 case relatives, and 921 control relatives. IBS cases had a median age of 50 and 83% were women. Of IBS cases, 74% had experienced any general trauma compared to 59% among controls, yielding an odds ratio of 1.56 (95% CI: 1.13–2.15, p < 0.008). There were no statistical differences between IBS relatives and control relatives with regards to lifetime trauma. Conclusions & Inferences IBS is associated with childhood trauma, and these traumas often occur prior to onset of IBS symptoms. This provides further insight into how traumatic childhood events are associated with development of adult IBS.